A new Colombian species in the milliped genus Psammodesmus, symbiotic host for bryophytes (Polydesmida: Platyrhacidae) - Hoffman, Richard L.; Martinez, Daniela; D., Eduardo Florez (Zootaxa, 2011)
The name Psammodesmus bryophorus is proposed for an ornate platyrhacid milliped discovered in a transitional AndeanPacific montane rainforest in Nariño Department, Colombia. This species is remarkable for being the first milliped known to be host of ectocommensal mosses (10 species belonging to 5 families including especially Pilotrichaceae and Lejeuneaceae) that grow on the milliped’s dorsum The species is likewise of interest in that the male genitalia are similar to those of the Ecuadorian Psammodesmus fasciolatus Silvestri, while peripheral structures differ in a number of details. Both species are described and illustrated from type material. The effect of this situation on future conduct of platyrhacid taxonomy is highlighted.